Impact of a high-fat, low-carbohydrate ketogenic diet on seizure frequency in children with drug-resistant epilepsy: a systematic review and Meta-analysis - Liu, Jian; E, Ri-He-Mu-Qi-Qi-Ge; Zhang, Jia-Qi; Wang, Da-Peng (Frontiers in Nutrition, 2025)
BackgroundDrug-resistant epilepsy in children poses significant therapeutic challenges. The ketogenic diet (KD), characterized by high-fat and low-carbohydrate content, has emerged as a potential adjunctive treatment. This meta-analysis aimed to systematically evaluate the impact of the KD on seizure frequency in pediatric patients with drug-resistant epilepsy.MethodsFollowing PRISMA guidelines, PubMed, Embase, Web of Science, and the Cochrane Library were searched to identify randomized and quasi-randomized trials of classical KD, modified Atkins diet (MAD), and low-glycemic-index treatment (LGIT) in children (≤18 years) with DRE. Two reviewers independently screened studies, extracted data, and assessed quality using the Cochrane Risk of Bias Tool 2.0. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using fixed- or random-effects models.ResultsNine studies met the inclusion criteria. For patients achieving >50% seizure reduction, pooled analysis (random-effects model; I2 = 60.5%, p = 0.009) revealed an OR of 7.69 (95% CI [3.42, 17.3]). Analysis of studies reporting >90% seizure reduction (fixed-effects model; I2 = 0.0%, p = 0.749) yielded an OR of 8.54 (95% CI [3.13, 23.31]). In the subset evaluating seizure freedom, the pooled OR was 7.35 (95% CI [2.17, 24.88]) with minimal heterogeneity (I2 = 4.4%, p = 0.371). Subgroup analyses favored the classical KD and interventions ≥6 months. Sensitivity analysis confirmed result stability, and Egger’s test indicated no significant publication bias (p > 0.05), although the test had limited power due to the small number of included studies. The most frequent adverse events were constipation (37.5%), anorexia (19.5%), and diarrhea (18.9%).ConclusionThe KD significantly improved seizure outcomes, with robust efficacy in reducing seizure frequency and a higher likelihood of achieving seizure freedom, although absolute rates of seizure freedom were modest. These findings support the KD as a promising adjunctive therapy for children with drug-resistant epilepsy; however, further large-scale, long-term studies are needed to confirm its sustained efficacy and safety.Systematic review registrationCRD420251122427.